2012
DOI: 10.1186/1471-2407-12-297
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for colorectal cancer surgery and care according to patient-, tumor-, and hospital-related factors

Abstract: BackgroundColorectal cancer (CRC) care has improved considerably, particularly since the implementation of a quality of care program centered on national evidence-based guidelines. Formal quality assessment is however still needed. The aim of this research was to identify factors associated with practice variation in CRC patient care.MethodsCRC patients identified from all cancer centers in South-West France were included. We investigated variations in practices (from diagnosis to surgery), and compliance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
0
23
1
3
Order By: Relevance
“…The overall operability among our patients (90 %) was lower than other studies (97 %) [19]. However, the operability among those patients undergoing emergency procedures was only 65 %, a finding that has not been reported earlier.…”
Section: Surgery (Overall)contrasting
confidence: 53%
See 3 more Smart Citations
“…The overall operability among our patients (90 %) was lower than other studies (97 %) [19]. However, the operability among those patients undergoing emergency procedures was only 65 %, a finding that has not been reported earlier.…”
Section: Surgery (Overall)contrasting
confidence: 53%
“…Eighty percent of deaths followed surgery for rectal cancer. Mortality as high as 13% has been reported following emergency procedures while that reported for elective procedures is around 2% [19]. In these studies it is not clear if post-operative mortality was procedure related or due to other co morbid factors.…”
Section: Open Surgery Vs Laparoscopymentioning
confidence: 45%
See 2 more Smart Citations
“…A strong decrease in guideline concordance related to patient age was evident, with the adjuvant chemotherapy rate dropping from 90% for patients less than 60 years of age to 20% for patients 80 years of age and older (data not shown). A French study conducted in 2002-2003 found that, after controls for other possible factors had been applied, the use of chemotherapy dropped significantly for patients 75 years of age and older 8 .…”
Section: Methodsmentioning
confidence: 99%